IMPACT DUE TO MICROPLASTICS POLLUTION IN COASTAL ENVIRONMENT ALONG CHENNAI COAST - Somasundaram Ramesh 1, R. Nagalakshmi 1 (Chelonian Research Foundation, 2023)
The presence of micro plastics in aquatic environments is becoming a growing concern with serious potential impact for both ecosystems and human health. To investigate this problem, we conducted a random sampling to measure the presence and distribution of micro plastics in the coastal waters along Chennai, India. Water and sediment samples are collected from five different locations and also using Fourier transform infrared spectroscopy (FTIR). The results revealed that micro plastics are found in all samples, with the highest concentration in sediment samples. The findings provided evidence of the pervasive nature of micro plastics in the marine water of Chennai, and highlighted the need for management strategies to address the risks micro plastics present to both ecosystems and public health. Keywords: Microplastics; Aquatic environment; Chennai coast; Pollution; Sustainable practices.